An economic analysis of the family - Ermisch, John (Princeton University Press, 2003)
What do economists have to say about behavior within the context of the family? This book improves our understanding of how families and markets interact, why important aspects of families have been changing in recent decades, and how families respond to, and are affected by, public policy. It covers a broader range of topics with more consistency than have previous studies, including all major theoretical developments in the field over the past decade. John Ermisch builds his analysis on the premise that the standard analytical methods of microeconomics can help us understand resource allocation and the distribution of welfare within the family. Families are dynamic institutions--and so the author uses these same methods to study family formation and dissolution (including marriage, fertility, and divorce) and household formation, as well as intergenerational transfers, household production and investment, and bargaining between family members. He also shows how economic theories of the family can help guide and structure empirical analyses of demographic and related phenomena, such as labor supply, child support, and returns to education. Examples of studies that apply the theory are provided throughout the book. The most comprehensive and up-to-date introduction to an increasingly dynamic area of research, one with important implications for public policy, An Economic Analysis of the Family will be a valuable resource for advanced students of microeconomics and also for students and researchers in sociology, psychology, and other social sciences.